Effect of computerized cognitive remediation therapy on mental time travel in patients with schizophrenia— a pilot randomized controlled trial - Cao, Junhua; Zhou, Cao (Frontiers in Psychiatry, 2024)
Objective To investigate the intervention effect of computerized cognitive remediation therapy (CCRT) on mental time travel (MTT) in patients with schizophrenia(SCZ). Methods From August 2020 to July 2021, 60 patients with SCZ were randomly allocated to either the study or the control group. The control group was treated with conventional drugs alone. The study group received CCRT and medical therapy for 40 minutes three times a week for 4 weeks. The participants underwent the MTT test before and after the training. Results A total of 28 patients in the study group and 26 patients in the control group were included in the analysis. Before training, there was no significant difference in the concretization ratio of recalling past and imagining future events between the study group and the control group (P > 0.05). After 4 weeks of training, the specific event ratio of the study group was higher than that of the control group (P < 0.01). In terms of the emotional titer of the events, the concreteness of the positive events in the study group was higher than that of the neutral events and negative events (P < 0.01). The concreteness of negative events was higher than that of neutral events (P < 0.01). Conclusion CCRT can improve the MTT ability of SCZ patients, which is manifested by an increase in the concretiveness of recalling past and imagining future events.